2021
DOI: 10.1159/000520311
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Its Analogs as Potential Epigenetic Modulators: Prevention of Diabetes and Its Complications

Abstract: <b><i>Background:</i></b> The pathobiology of diabetes and associated complications has been widely researched in various countries, but effective prevention and treatment methods are still insufficient. Diabetes is a metabolic disorder of carbohydrates, fats, and proteins caused by an absence of insulin or insulin resistance, which mediates an increase of oxidative stress, release of inflammatory factors, and macro- or micro-circulation dysfunctions, ultimately developing into diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…It has been found that this DNA methylation inhibitor has been widely used in metabolic diseases such as cancer, asthma and diabetes ( Boyanapalli and Kong, 2015 ). In a study of curcumin’s ability to regulate blood glucose by inhibiting DNA methylation, researchers found that curcumin can reduce inflammation and oxidative stress in diabetic patients by reducing IL-1β, TNF-α and ROS levels in the body, which can lead to damage to pancreatic β-cells and reduced insulin secretion, resulting in increased blood glucose levels in patients ( Tang et al, 2022 ). Similar to curcumin, the active substance in mulberry leaf can regulate blood glucose by regulating the levels of oxidative stress and inflammatory factors in the body, thereby protecting pancreatic islet cells, a result similar to that of curcumin.…”
Section: Epigenetics Diabetes Mellitus and The Link Between Mulberry ...mentioning
confidence: 99%
“…It has been found that this DNA methylation inhibitor has been widely used in metabolic diseases such as cancer, asthma and diabetes ( Boyanapalli and Kong, 2015 ). In a study of curcumin’s ability to regulate blood glucose by inhibiting DNA methylation, researchers found that curcumin can reduce inflammation and oxidative stress in diabetic patients by reducing IL-1β, TNF-α and ROS levels in the body, which can lead to damage to pancreatic β-cells and reduced insulin secretion, resulting in increased blood glucose levels in patients ( Tang et al, 2022 ). Similar to curcumin, the active substance in mulberry leaf can regulate blood glucose by regulating the levels of oxidative stress and inflammatory factors in the body, thereby protecting pancreatic islet cells, a result similar to that of curcumin.…”
Section: Epigenetics Diabetes Mellitus and The Link Between Mulberry ...mentioning
confidence: 99%
“…However, the curcumin treatment of high glucose-induced cells stimulates HDAC activity, particularly HDAC2, while reducing HAT activity, particularly p300, resulting in the deacetylation of p65 NF-B and, as a result, the suppression of proinflammatory cytokine production. Therefore, the role of curcumin supplementation in the regulation of the DNA methylation, histone acetylation, and miRNAs of genes involved in insulin signaling and inflammation in individuals with T2D suggests a potential role for curcumin in preventing T2D through epigenetic mechanisms [99].…”
Section: Functional Foods With Preventive Epigenetic Effects In T2dmentioning
confidence: 99%
“…Curcumin is a characteristic component of CLR and exhibits anti-infammatory, antioxidation, antitumor, and immunoregulatory properties. Moreover, it improves insulin resistance, obesity, and other FFA-related diseases [11,[28][29][30][31]. In this study, isoquercetin and rutin were also screened as representative compounds.…”
Section: Identifcation Of Prototypes and Metabolites Of Xrg-4 Inmentioning
confidence: 99%